2004
DOI: 10.1103/physrevlett.92.186404
|View full text |Cite
|
Sign up to set email alerts
|

Realization of an Interacting Two-Valley AlAs Bilayer System

Abstract: By using different widths for two AlAs quantum wells comprising a bilayer system, we force the X-point conduction-band electrons in the two layers to occupy valleys with different Fermi contours, electron effective masses, and g-factors. Since the occupied valleys are at different X-points of the Brillouin zone, the interlayer tunneling is negligibly small despite the close electron layer spacing. We demonstrate the realization of this system via magneto-transport measurements and the observation of a phase-co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
128
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(146 citation statements)
references
References 32 publications
18
128
0
Order By: Relevance
“…We have also succeeded in fabricating 2DESs confined to narrow (< 5 nm-wide) AlAs QWs where the electrons occupy the Z valley. 9 The lowtemperature mobility in this case is limited by interface roughness scattering; 13 nevertheless, we have achieved the highest mobilities yet reported, ~ 5 × 10 4 cm 2 /Vs. 9,13 This is more than an order of magnitude larger than the highest previously reported mobility values for similar types of samples 6 and comparable to the highest mobilities reported in Si-MOSFET 2DESs.…”
Section: Fabrication Of High-mobility 2d Electrons In Alas Quantum Wellsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have also succeeded in fabricating 2DESs confined to narrow (< 5 nm-wide) AlAs QWs where the electrons occupy the Z valley. 9 The lowtemperature mobility in this case is limited by interface roughness scattering; 13 nevertheless, we have achieved the highest mobilities yet reported, ~ 5 × 10 4 cm 2 /Vs. 9,13 This is more than an order of magnitude larger than the highest previously reported mobility values for similar types of samples 6 and comparable to the highest mobilities reported in Si-MOSFET 2DESs.…”
Section: Fabrication Of High-mobility 2d Electrons In Alas Quantum Wellsmentioning
confidence: 99%
“…9 The lowtemperature mobility in this case is limited by interface roughness scattering; 13 nevertheless, we have achieved the highest mobilities yet reported, ~ 5 × 10 4 cm 2 /Vs. 9,13 This is more than an order of magnitude larger than the highest previously reported mobility values for similar types of samples 6 and comparable to the highest mobilities reported in Si-MOSFET 2DESs. 14 And again, the samples reveal novel behavior, e.g., an interaction-induced enhancement of the spin-susceptibility at low densities that is the largest among all 2DESs and is remarkably close to that of an ideal, interacting 2DES.…”
Section: Fabrication Of High-mobility 2d Electrons In Alas Quantum Wellsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the highly interacting, dilute regime (r s > ∼ 3), χ * and m * are typically enhanced compared to the band values and increase with increasing r s , as confirmed both theoretically [1][2][3][4][5][6][7][8] and experimentally. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Besides r s , the spin and/or valley degrees of freedom also play an important role in the re-normalization of m * and χ * since they modify the exchange interaction. 5,6,17,[24][25][26][27] In particular, it was recently demonstrated that when a 2D electron system is fully spin and valley polarized, m * is suppressed compared to its band value.…”
mentioning
confidence: 99%